Contractual Price Provisions and Their Determinants in Conditions of Uncertainty: The Case of Chilean Fruit Exports - Pavez, Iciar; Codron, Jean-Marie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2018)
This article analyzes the choice of export contracts of perishable goods. It draws on the Transactional Cost Theory, and particularly the literature of incomplete contracts. Using a 2014 database of 177,296 transactions and corresponding contracts performed by Chilean fruit exporters, together with qualitative information gathered from a field survey, we show through a binomial logit that the choice between firm sale and consignment is a function of the environmental uncertainty of the importing country, the temporal specificity of the transacted product and the frequency of transactions.